Quality of Life of Patients With Euthymic Bipolar Disorder and Its Associations With Demographic and Clinical Characteristics, Psychopathology, and Cognitive Deficits. Issue 1 (31st May 2013) - Xiang, Yu‐Tao; Li, Li‐Jun; Zhou, Jing‐Jing; Wang, Chuan‐Yue; Dixon, Lisa B.; Dickerson, Faith; Zhou, Fu‐Chun; Ungvari, Gabor S.; Zhang, Xiang‐Yang; Shum, David H. K.; Au, Raymond W. C.; Tang, Wai‐Kwong; et al.
<x xml:space="preserve">Abstract</x> Purpose Little is known about quality of life (QOL) in Chinese patients with bipolar disorder (BD) in remission (euthymia). This study examined the QOL of such a cohort of BD patients and its demographic, clinical, and cognitive correlates. Design and Methods Forty‐seven euthymic BD patients and 47 matched healthy controls formed the study sample. Socio‐demographic characteristics, prospective memory, retrospective memory, intelligence quotient, and executive functioning were measured in all participants together with patients' psychopathology ratings. Findings Multivariate analyses revealed that compared to controls, euthymic BD patients had significantly lower satisfaction with physical QOL domain. Only subthreshold depressive symptoms independently contributed to reduced satisfaction with physical and environmental QOL domains, whereas no variable predicted its psychological and social domains. Practice Implications Contrary to findings from Western settings, demographic variables and cognitive deficits had no associations with any QOL domain in euthymic Chinese BD patients. Control of subthreshold depressive symptoms in euthymic BD patients might enhance their QOL.